2000
DOI: 10.1091/mbc.11.2.481
|View full text |Cite
|
Sign up to set email alerts
|

Role for Dynamin in Late Endosome Dynamics and Trafficking of the Cation-independent Mannose 6-Phosphate Receptor

Abstract: It is well established that dynamin is involved in clathrin-dependent endocytosis, but relatively little is known about possible intracellular functions of this GTPase. Using confocal imaging, we found that endogenous dynamin was associated with the plasma membrane, the trans-Golgi network, and a perinuclear cluster of cation-independent mannose 6-phosphate receptor (CI-MPR)-containing structures. By electron microscopy (EM), it was shown that these structures were late endosomes and that the endogenous dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
71
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(84 citation statements)
references
References 66 publications
10
71
0
Order By: Relevance
“…Thus, we incubated ultracryosections of CHC antisense RNA-expressing cells with an anti-dynamin antibody (Hudy 1). This antibody not only labeled the clathrin coats as reported (16,18), but also the tubular structures (Fig. 3 C-E).…”
Section: Chc Antisense Rna Leads To Accumulation Of Clathrin-coated Psupporting
confidence: 62%
See 3 more Smart Citations
“…Thus, we incubated ultracryosections of CHC antisense RNA-expressing cells with an anti-dynamin antibody (Hudy 1). This antibody not only labeled the clathrin coats as reported (16,18), but also the tubular structures (Fig. 3 C-E).…”
Section: Chc Antisense Rna Leads To Accumulation Of Clathrin-coated Psupporting
confidence: 62%
“…The cells were washed with PBS and fixed with 0.1% glutaraldehyde and 2% formaldehyde in 0.1 M phosphate buffer, pH 7.2, followed by dehydration and embedding in Epon. Alternatively, the fixed cells were processed for ultracryosections and subsequent ImmunoGold labeling to localize dynamin (16). In some experiments, cells were fixed in the presence of ruthenium red (0.5 mg͞ml) before they were washed and embedded in Epon (16).…”
Section: Sorting and Processing Of Cathepsin Dmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the work with the dynamin specific GTP hydrolysis inhibitor dynasore, it was recently proposed that dynamin may in fact act at two different stages in clathrin-vesicle formation, (Macia et al, 2006). Using dynasore, the authors observed the arrest of clathrin-coated vesicle formation at two different stages, both Dynamin has been demonstrated to be involved in recycling from early endosomes to the TGN (Nicoziani et al, 2000) and dynamin has also been shown to be recruited to early endosomal clathrin coats upon overexpression of the endosomal sorting-protein Hrs (Raiborg et al, 2001a). Recycling of the TfR has been proposed to follow two distinct pathways, one pathway where dynamin is involved in transport from the early endosome to the recycling endosome, and another pathway different from that via the recycling endosome (van Dam et al, 2002).…”
Section: Dynaminmentioning
confidence: 99%